ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДА КӨРКЕМ-ҲҮЖЖЕТЛИ ОЧЕРКТИҢ ӨЗГЕШЕЛИКЛЕРИ - Жәримбетова, Т.Қ. (SCIENCE and SOCIETY, 2024)
The article presents scientific and theoretical views expressed by scientists in literary essays of Karakalpak literature. In order to determine its genre features, the formation of its theoretical concepts and plot-shaped illumination in an artistic and documentary essay, it was studied through the presentation of the event and the skill of the writer. Having shown the truth in its state or brought it into artistic form, written works were compared and obtained the necessary results.
Keywords: essay; artistic-documentary essay; real character; portrait; image